Processo de desenvolvimento de produto sob a perspectiva da gestão do design - Costa, Sara Giordana (Universidade do Vale do Rio dos Sinos, 2014)
The objective of this case study is to perform a reassessment of the shoes development process, from the perspective of the management and the design tools, encompassing the strategic relationship with the other sectors of the company, along with the Products Department, reinforcing the important role of the designer as a mediator between the market and the industry, as well as the design as a component of the entrepreneurial culture. The constant demand for new markets in increasingly dynamic and complex scenarios, along with the importance of recognizing warning signs and consumer trends, urges a new and comprehensive understanding of the development process, not only as a linear setting of sequential activities. The concepts of strategy, management and design relate with each other when all of them converge objectives as problem solvers, adding value for the company and consumers. The Design Management provides the combination and coordination of those concepts, empowering the company with a project culture concept that reaches far beyond the single perspective of product development, Therefore, the design management can be understood as a manageable and continuous process that provides better consumer experiences, making the connections between the company and the market.
Keywords: Desenvolvimento; Produto; Design; Gestão; Projeto; Development; Product; Management; Project